Perancangan Sistem Pengelolaan Zakat Masjid Jami Al-Muhajirin Berbasis Web Menggunakan Metode Research and Development (R & D) - Bagas Prayoga; M. Iwan Wahyudin; Agus Iskandar (LPPM STIKI MALANG, 2021)
Technology is increasingly advanced and developing, especially in this modern era, people want things that are practical. This application system is also very much needed in the future in managing zakat at the Jami Al-Muhajirin Mosque and making it easier to pay online. The aim of the author to achieve is to produce a web-based zakat management system at the Jami al-Muhajirin mosque by using the R&D method of application systems in web-based zakat management at the Jami al-Muhajirin mosque to facilitate the management of mosque zakat and can help facilitate the Jami al-Muhajirin mosque committee. -muhajirin in collecting data and making it easier for muzakki to pay online. The function of the R&D method used to create a particular application and the success of the web. The final results of testing zakat payers no longer need to come to the mosque because they can use the website and the committee can make it easier to collect zakat payment reports with the website.